Energy Utilization Analysis and Optimization of Corrective Insoles Manufactured by 3D Printing - Andrew Rees (Sustainable Design and Manufacturing 2020, 2020)
The foot orthotic insole market is forecast to surpass a value of 3.6 billion USD by 2021. This vast industry continues to rely on foam milling and other subtractive methods of manufacturing, which have proven to be wasteful and inefficient. Leaps in digital manufacturing have enabled the technology to enter a plethora of industries, with the promise of increased customization accompanied with reduced waste generation. Despite boasting these valuable traits, the explosive proliferation of 3D printing in conjunction with mounting pressure to incorporate sustainable practices, means that research must be focused on maximizing the material and energy efficiency of the technology. This paper employs a Design of Experiments (DoE) approach for the optimization of two prefabricated insoles, adjusting percentage infill and layer height to obtain data regarding the effects of these parameters on print time, filament usage volume, and energy consumption. Key conclusions formed from the study were that infill density is the dominant factor effecting material consumption and power usage, whereas layer height has the greatest influence on production time. The data presented in this study has the potential to aid not only in the development of mass producible additive manufactured (AM) insoles, but also to advance the understanding of the environmental impact of AM technologies.